Praktik Cuci Tangan Pada Anak TK Di TK Negeri Pembina Jayapura - Elisabet Bre Boli; Febriana Astuti; Charisa Sanggenafa; Cinta Resti Manda; Yerlin Wakerwa; Asalin Wantik; Jesika Helen Assa; Fince Tenouye; Elsya Wandikbo; Frans Pebby Kogoya; Selvina Jitmau; Dwi Astuti; Christy Wattimena; Istiana Dyah Lestari; Monaliza Heriyanti Kende (STIKES Columbia Asia Medan, 2026)
Breastfeeding should ideally begin immediately after birth and be provided exclusively for the first six months of life. However, in 2022, the coverage of exclusive breastfeeding among infants aged 0–6 months in Jayapura was only 21%, which remains far below the national target of 45%. Various factors contribute to this low coverage, including limited knowledge, lack of experience, insufficient support systems, and concerns among adolescent mothers that breastfeeding may interfere with their education or employment. This study aimed to explore the breastfeeding experiences of adolescent mothers in Wahno Village, Abepura Subdistrict. A qualitative research design was used, with structured interviews conducted using a questionnaire. The results indicated that the initiation of exclusive breastfeeding among adolescent mothers was generally positive. Participants reported mixed emotional experiences, including feelings of happiness, pride, stress, and discomfort. Family support, particularly from husbands, played an important role in sustaining breastfeeding practices. Most respondents also demonstrated adequate knowledge regarding how to manage breastfeeding-related challenges. Overall, adolescent mothers in Wahno Village showed a reasonable level of understanding and commitment toward exclusive breastfeeding. Continued education and support are recommended to further strengthen breastfeeding practices among adolescent mothers and their families.